Changes in Therapeutic Hypothermia and Coronary Intervention Provision and In-hospital Mortality of Patients With Out-of-Hospital Cardiac Arrest: A Nationwide Database Study. Issue 6 (December 2016) - Tagami, T.; Matsui, H.; Fushimi, K.; Yasunaga, H.
Abstract : (Abstracted from Crit Care Med, 44:488–495, 2016) Between 2008 and 2012, Japanese researchers examined the cases of adult patients with out-of-hospital cardiac arrest (OHCA) with 2 goals in mind. First, they sought to ascertain if there was a trend toward postresuscitation care in this patient population, by means of therapeutic hypothermia and coronary intervention.